FIGURE 3 in Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica) - Peña Cantero, Álvaro L. (Zenodo, 2021)
FIGURE 3. Oswaldella vervoorti Peña Cantero & García Carrascosa, 1998: A–B, G, hydrocladial internode showing hydrotheca and mesial inferior nematotheca; C–D, H hydrotheca (lateral view) and mesial inferior nematotheca; E, hydrotheca (frontal view) and aperture of mesial superior nematophore (arrow); F, cauline apophysis with mamelon (arrow); I, gonotheca and two unforked hydrocladial internodes. (A, C–D, I, from NIWA 144253; B, F from NIWA 144249; E, G-H, from NIWA 144255). Scale bar: 100 µm (C–F, H), 200 µm (A–B, G, I). : Published as part of Peña Cantero, Álvaro L., 2021, Additions to knowledge of the biodiversity of benthic hydroids (Cnidaria: Hydrozoa) in the Balleny Islands (Antarctica), pp. 321-336 in Zootaxa 4966 (3) on page 333, DOI: 10.11646/zootaxa.4966.3.4, http://zenodo.org/record/4736691